GAMBARAN OHI-S SERTA PERILAKU MENYIKAT GIGI PADA PELAKU WISATA DI OBYEK WISATA TANAH LOT KABUPATEN TABANAN TAHUN 2016 - I G Ayuni Dwi Yanthi; Sagung Agung Putri Dwiastuti (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
Tourism has very multidimentional properties, not only related to economi, environmental and other dimensions, but also related to health problems. Health behavior consist of covered behavior as knowledge and attitudes towards health and behavior of the open form of action or practice of health. The aim of this study is to describe the OHI-S and toothbrusing behavior of tourism object in Tanah Lot Tourism object in June 2016. The kind of this study is descriptive method with survey program and direct examination to tourism object. Based on the result of research on tourism subject in Tanah Lot tourism object, the percentage of dental and oral hygiene with bad category most that (57,3%) medium (42,7%) and no respondent has OHI-S with good criteria. The average level of oral and dental hygiene is 3,34 tourism subject including for bad criteria. The percentage of brusing behaviour shows thar from 68 respondent who have toothbrusing behaviour with the highest criteria of guidance needed of 61 respondents (89,7%) sufficient criteria 6 respondents (8,8%) and least good criteria only 1 respondent (1,5%).